Croatia’s New Linear Tuition System: Students’ Friend or Foe? - Brajkovic, Lucia (International Higher Education, 2015)
A unique political situation predating Croatia’s ascension to the European Union, along with countrywide student protests, led to the adoption of a linear tuition model in which students are exempt from any tuition payment during their first year of college. After the first year, they are charged tuition according to merit-based criteria. This article discusses the benefits and potential unintended consequences of this policy, as well as the possible adoption of this model by other countries.